Conflicting histories and histories of conflict: Performing remembrance of the Algerian War in Didier Daeninckx's Le Bourreau et son double (1986). Issue 3 (1st September 2022) - Gleeson, John
Abstract : This article focuses on French author Didier Daeninckx's 1986 crime novel Le Bourreau et son double ['The Hangman and His Double']. Daeninckx's novel challenged official narratives that minimized the use of torture during the Algerian War and highlighted the brutalization of conscripted soldiers, the conflict's hidden victims. Firstly, this article investigates Daeninckx's use of what Max Silverman (2013) terms palimpsestic memory to highlight the interconnections between France's process of decolonization throughout the 1960s, and 1980s France, which saw a rise in urban poverty and racism and a severe decline in left-leaning politics. Secondly, palimpsestic memory is closely associated with intertextuality and this article examines Daeninckx's allusions to Georges Perec's W ou le souvenir d'enfance (1975) [ W, or the Memory of Childhood (1988)], which shares a similar structure and the themes of haunting and repressed memories with Le Bourreau et son double . Finally, the article emphasizes the value of popular culture, such as crime fiction, in the remembrance of hidden conflicts.